Terre et propriété à l'est de l'Europe depuis 1990 Faisceau de droits, relations de pouvoir - Maurel, Marie-Claude (Les Cahiers de la MSHE Ledoux, 2021)
The book traces the conditions for the restoration of private ownership of land, before analysing the recomposition of ownership relations and modes of land use in the aftermath of the fall of the communist systems.The concentration of agricultural structures is driven by fierce social competition to recover, capture, and then gather the "bundle of rights" of ownership over land as well as over the capital of exploitation. Seized in its multiple historical, legal, economic and political dimensions, the transformation of property regimes accompanies a reconfiguration of power relations that testifies to the emergence of a new agrarian capitalism.